A Longitudinal Study to Explore the Impact of Preservice Teacher Health Training on Early Career Teachers' Roles as Health Promoters. (September 2016) - Byrne, Jenny; Pickett, Karen; Rietdijk, Willeke; Shepherd, Jonathan; Grace, Marcus; Roderick, Paul
Teachers play a key role in promoting children and young people's health and therefore require health training during their initial teacher education (ITE). However, little is known about the impact of such training on teachers' knowledge, attitudes, confidence, and competence toward promoting health in school, especially long term. We report on Phase 1 of an 18-month project examining the long-term impact of an innovative health education program, based on socio-constructivist learning and critical reflection, during preservice teacher training at one ITE university in England. It also explored barriers and facilitators to promoting health in school. We sent a questionnaire to 1, 014 primary and secondary school teachers from three consecutive cohorts: preservice teachers ( N = 334), newly qualified teachers ( N = 334), and early careers teachers ( N = 346). Of these, 164 (16%) responded (32% of preservice teachers, 8% of in-service teachers). This low response rate presents limitations but is in accordance with other research following up early career teachers. The majority of the respondents found the training useful, felt confident and knowledgeable teaching and dealing with health issues, and held positive attitudes about promoting health. They indicated that practical experience, supportive colleagues, and a positive school ethos toward children's health and well-being were important facilitators to teaching health education. We conclude the training is associated with a positive, long-term effect in the minority who responded, and we argue that the socio-constructivist nature of the health education training is a contributor. However, school environment factors might mitigate or support the impact of training provided during ITE.